PENGARUH TINGKAT PENDIDIKAN DAN POLA ASUH ORANG TUA TERHADAP MORALITAS ANAK DI DESA LAWANGANAGUNG KECAMATAN SUGIO KABUPATEN LAMONGAN - Arlis Noviantika Dwimita (Universitas Negeri Surabaya (Unesa), 2023)
This study aims to determine the influence of the level of education and parenting patterns on the formation of children's moralitase in Lawangangung Village, Sugio district. The research approach used is descriptive quantitative. Data were collected using questionnaires (questionnaires) Sampling techniques using probability sampling. The number of samples studied was 30 biological parents who had children aged 12-17 years. Data analysis to test hypotheses using statistical analysis of multiple linear regression through partial testing (t test) and determinant coefficient testing (rsquare ) with a significance level of 0.05 using the help of SPSS 25 for windows. There were three variables in this study on education level (X1), parenting (X2), and child moralitas formation (Y). The results showed that there was a significant positive influence of the influence of education level and parenting on the moralitas formation of children, shown from the results of the t count test of 2.347 with a significant 0.027. Based on research on the level of education of good parents, discipline and wisdom will result in better parenting. This is driven by the need for encouragement and efforts to improve the quality of parenting towards the formation of children's moralitass so that there is a wholeness and harmony, so that the process and out put education can be maximized. The positive influence is that if the level of education of parents is better at educating, the better the results of parenting on the moralitas formation of children.